Managing Social Work According to the Educational Philosophy of Ho Chi Minh City University of Technology and Education - Thuy, Nguyen Thi Nhu (VNU Journal of Science: Education Research; Vol 36 No 1, 2020)
This article helps administrators, social workers to see the reality and difficulties in organizing, managing and implementing social activities for students at the Ho Chi Minh City University of Technical and Education  - a school that does not specialize in social work, but there are diverse and diversified community-oriented activities.